Traditions of the Organization and their Importance for the Formation of the Organizational Culture of Service Enterprises ("Journal "U". Economy. Management. Finance.", 2017)
The traditions of the organization are a significant factor in the formation of a stable organizational culture and an important source of the enterprise’s stability. This is due to the fact that the company's profit depends not only on competent management, but also on the ability of employees to follow the cultural norms prevailing in the organization. The study examined the essence of the organizational culture and their significance for the formation of organizational culture of companies in any field of activity, identified factors influencing their implementation and maintenance.
Keywords: organizational culture; сultural traditions of the organization; standards; values; services sector